THE MODERATION EFFECTS OF ACCESS TO FINANCE ON THE IMPACT OF MARKET ORIENTATION AND ENTREPRENEURIAL ORIENTATION ON THE PERFORMANCES OF SMES IN NIGERIA - Kabiru Sa’ad Sa’id; Sulaiman Ibrahim Kassim; Asmat Nizam Abdul Talib; Abubakar Adamu Magaji (Journal of Business Management and Accounting)
Nigerian Small and Medium Enterprises (SMEs) are the biggest business industry and a bedrock of the country’s economic development. However, few studies have been conducted on strategic orientation to improve performance. Therefore, this paper determines the effect of strategic orientations on the SMEs performance in Nigeria, which plays an imperative role in the nation's growth. The rareness of this study focuses on access to finance, which is central for SMEs to progress and to compete in domestic and global markets. The main purpose of this study is to investigate the moderating influence of access to finance on the nexus between market orientation, entrepreneurial orientation, and SMEs’ performance in Nigeria. The surveys were administered to 300 owners and managers of SMEs in NorthWest Nigeria. A total of 251 effective responses, or 83.66% of the response rates, were put for data analysis. The finding indicated that entrepreneurial orientation and access to finance have a significant effect on SMEs' performance. However, market orientation has indicated a non-significant effect on SMEs' performance. In addition, access to finance has shown a non-significant moderating effect on both market orientation and entrepreneurial orientation on SMEs' performance. The research implication shows that managers should focus more on entrepreneurship orientation.